Investigations on Adenosine Diphosphate (ADP) Induced Platelet Adhesiveness in Vitro* Part II. Studies on the Mechanism - Skålhegg, B. A; Hellem, A. J; Ödegaard, A. E (Thrombosis and Haemostasis, 1964)
An attempt to clarify the ADP platelet reaction has been done by investigating the effect of substances which inhibit the reaction in vitro. The inhibitors used may be divided into two groups. Monoiodo acetic acid, molecular iodine, para-chloro mercuribenzoic acid and potassium ferricyanid lead to noncompetitive inhibition. Substances containing free -SH groups and adenine conjugates show competitive inhibition.The primary bleeding time is prolonged when wounds are flushed with solutions of these compounds.It is shown that adenosine tetraphosphate aggregates platelets in the same manner as ADP.Based upon these observations an attempt is made to explain some of the steps involved in the ADP platelet reaction.